2017
DOI: 10.1051/shsconf/20173413003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corporate Governance in Firm Performance

Abstract: Abstract. The objective of this study is to examine the role of corporate governance to increase firm performance. The measure of corporate governance are corporate governance mechanism and Corporate Governance Perception Index (CGPI). Samples are companies that followed CGPI award at 2005-2014. The examination of the relationship of corporate governance and firm performance is conducted by regression of corporate governance mechanism variables and control variables to profitability. Corporate governance mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 20 publications
2
17
0
2
Order By: Relevance
“…Chan and Li (2008) found a positive relationship between the independence of the audit committee and company performance. Similarly, Kallamu and Saat (2015) and Naimah (2017) found a positive association between independent audit committee members and profitability a proxy for company performance. Therefore, a positive association between audit committee independence and company performance is expected and justified; thus, the following hypothesis is proposed:…”
Section: Independence Of Audit Committeementioning
confidence: 87%
“…Chan and Li (2008) found a positive relationship between the independence of the audit committee and company performance. Similarly, Kallamu and Saat (2015) and Naimah (2017) found a positive association between independent audit committee members and profitability a proxy for company performance. Therefore, a positive association between audit committee independence and company performance is expected and justified; thus, the following hypothesis is proposed:…”
Section: Independence Of Audit Committeementioning
confidence: 87%
“…Audit committees through their oversight role (Alqatamin, 2018), contribute significantly towards shaping the governance tone of the organization, by complementing and strengthening internal audit functions. However, the degree of influence of the committee also dependent on its attributes, the main ones being the committee's expertise mix (Aldamen, et al, 2012;Enofe, et al, 2013), independence (Nekhili, et al, 2016;Naimah, 2017;Alqatamin, 2018) and the conduct of the committee's meetings (Jackling & Johl, 2009;Hsu & Petchsakulwong, 2010;Alqatamin, 2018). These attributes are key in determining the capacity of the audit committee to influence the effectiveness of internal audit function and directing the overall governance tone of the entire organization.…”
Section: Discussionmentioning
confidence: 99%
“…Audit committee independence can be enhanced by having majority of members being and the chairing of the committee by independent directors who has no personal or economic ties with management (Akhigbe & Martin, 2006;Larry & Taylor, 2012;Nekhili, et al, 2016), thereby strengthening their monitoring role and subsequently reducing agency problems (Yeh, et al, 2011). Notwithstanding the inconclusive nature of studies conducted on audit committee independence, a handful of literature notes the importance of audit committee independence in enhancing organizational performance Naimah, 2017;Alqatamin, 2018), and audit quality (Abbott & Parker, 2000;Abbott, et al, 2003;Khlif & Samaha, 2016;Lee & Fargher, 2018). However, Shamar et al (2009) argued that there is a downside risk associated with independent audit committees, noting that the committee members will be completely devolved from management and therefore have less exposure to critical issues affecting the daily operations of the organization (Sharma, et al, 2009).…”
Section: Audit Committee Independencementioning
confidence: 99%
“…Good corporate governance can control management and risk so as to have positive and significant impact on organizational performance [12]. There are many other studies which have shown that implementation of GCG is able to contribute to improving company performance such as Andriana & Panggabean find that GCG mechanism simultaneously have significant effect on financial performance [13], Ahmed & Hamdan found a positive influence of CG mechanism on performance [14], Naimah & Hamidah show that CGG positively influence profitability [15], Rahnama & Jalili also show that CG Index significantly impacts on the company performance [16], Yesser et al show that CG mechanisms have significantly positive relationship with ROE [12]. There are many other investigations have found that GCG has positively associated with the financial performance [17], GCG has positively related to the bank's profitability measure by ROA [18], in generally GCG has positive impact on all the performance indicators of an organization [19], the other result show that GCG has relationship with bank performance [20].…”
Section: Introductionmentioning
confidence: 99%